Down syndrome: Neurobiological alterations and therapeutic targets. (March 2019) - Vacca, Rosa Anna; Bawari, Sweta; Valenti, Daniela; Tewari, Devesh; Nabavi, Seyed Fazel; Shirooie, Samira; Sah, Archana N.; Volpicella, Mariateresa; Braidy, Nady; Nabavi, Seyed Mohammad
Highlights: Down syndrome is both a neurodevelopment and neurodegenerative disorder. Genetic and metabolic alterations involved in Down syndrome neuropathology are discussed. Drugs targeting altered genes and metabolic pathways for therapeutic challenge in DS are discussed. Abstract: Down syndrome (DS) is a genetic disease that occurs due to an aneuploidy of human chromosome 21. Trisomy of chromosome 21 is a primary genetic cause of developmental abnormalities leading to cognitive and learning deficits. Impairments in GABAergic transmission, noradrenergic neuronal loss, anomalous glutamatergic transmission and N -methyl-d -aspartate receptor signalling, mitochondrial dysfunction, increased oxidative stress and inflammation, differentially expressed microRNAs, increased expression of crucial chromosome 21 genes, and DNA hyper-methylation and hyperactive homocysteine trans-sulfuration pathway, are common incongruities that have been reported in DS and might contribute to cognitive impairment and intellectual disability. This review provides an update on metabolic and neurobiological alterations in DS. It also provides an overview of the currently available pharmacological therapies that may influence and/or reverse these alterations in DS.